Employment equity groups’ experience of inclusion and commitment to the CAF - Peach, Jennifer M.; Laplante, Joelle; Boileau, Kayla (Frontiers in psychology, 2024)
The Canadian Armed Forces (CAF) are subject to the Employment Equity Act, which requires federally regulated employers to identify and eliminate barriers to the employment of designated groups (women, Indigenous peoples, persons with disabilities (PwD), and racialized members), and establish short-term, numerical goals to address underrepresentation. Addressing employment barriers experienced by these equity seeking groups is one of the CAF’s key priorities. The objective of this study is to examine group differences in feelings of inclusion (i.e., relatedness, organizational inclusion, and microaggressions) and retention-related measures (i.e., job satisfaction, affective commitment, and intentions to leave), the contribution of feelings of inclusion to retention measures, and the effect of numerical representation and number of marginalized identities on these concepts. We analyzed data from the 2022 Your Say Matters survey, which was administered to a representative sample of CAF members, with oversampling of under-represented groups. Respondents included 4,483 Regular Force members (30.9% response rate). The groups under study included Indigenous members, persons with disabilities, racialized members, women not part of another group (non-Indigenous, non-racialized, women without disabilities), and everyone else (non-Indigenous, non-racialized, not women, without disabilities). Our hypotheses were supported overall, such that groups with less representation in the CAF scored lower on inclusion measures than groups with more representation. The number of marginalized identities held by military members predicted the inclusion measures, but did not predict retention-related measures. There were some group differences on retention-related measures, such that women not part of another group scored more favorably than other designated groups, and racialized members scored more favorably than PwD and Indigenous members. Inclusion measures predicted job satisfaction, affective commitment, and intentions to leave equally for all groups studied, suggesting that feeling included is important for all.